Evaluasi Aspek Gerakan dan Tingkat Kenyamanan Kapal Latih KM. Airaha 02 - Yani Nurita Purnawanti; Nurul Huda; Egbert Josua Sirait (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
KM. Airaha 02 is a training vessel owned by the Sorong Marine and Fisheries Polytechnic. This ship is a type of fishing vessel that has a weight of 169 GT, LOA 30.20 m and a width of 6.30 m. KM. Airaha 02 is capable of traveling at a speed of 12.5 knots. KM. Airaha 02 is equipped with long line tuna fishing gear and squid jigging, frozen fish hold, and freezing room. Safety and comfort of crew and passengers on KM. Airaha 02 really needs to be considered for the smooth operation of fishing operations. Therefore, it is necessary to analyze the evaluation of the ship's motion when traveling on random waves in order to calculate the comfort level of passengers based on ISO 2631 criteria. The analysis was carried out by reverse engineering. The 3D model is based on general arrangement data from KM. Airaha 02, the main measure, and direct survey results. The ship's motion due to wave excitation is obtained from the results of the RAO analysis, then the comfort level is carried out by the Motion Sickness Incident (MSI) analysis. The biggest movement experienced by KM Airaha 02 is surge of 2.8 m/m and roll of 6.1 deg/m. Passengers began to feel discomfort after 2 hours of travel when the waves came from the head seas direction. If the direction of the wave is coming from the side, passengers start to feel discomfort after 8 hours of travel.